ANALYSIS OF PSYCHO-SOCIAL FACTORS IN GENERAL ANXIETY DISORDER IN PATIENTS WITH PSORIASIS. (Vietnam Journal of Community Medicine, 2026)
Research objective: To analyze certain psychosocial factors associated with generalized anxiety disorder (GAD) in patients with psoriasis.Subjects and methods: A cross-sectional descriptive study was conducted on 236 patients diagnosed with psoriasis vulgaris who were examined and treated at the National Hospital of Dermatology and Venereology during 2025–2026.Results: Being single was associated with GAD (OR = 2.88; 95% CI: 1.02–8.10; p = 0.049), and perceived stigma was associated with GAD (OR = 6.49; 95% CI: 2.99–14.05; p < 0.001). No statistically significant associations were found regarding age, age of psoriasis onset, or disease duration.Conclusion: GAD is an issue requiring attention in patients with psoriasis. Perceived stigma is a factor associated with GAD, suggesting a need to integrate the screening and detection of GAD symptoms, the assessment of stigma experiences, and the provision of psychosocial support and supportive resources into the management of psoriasis patients.
Keywords: generalized anxiety disorder, psoriasis